Determinants DETERMINANTS OF GROSS REGIONAL DOMESTIC PRODUCT (GRDP) EVIDENCE FROM WEST NUSA TENGGARA, 2004-2023 - Rajak, Zulkifli; Wahidin, Wahidin; Fadlli, Muhammad Dzul (Journal of Finance, Economics and Business, 2025)
This study investigates the effects of labor, inflation, investment, and the Human Development Index (HDI) on the Gross Regional Domestic Product (GRDP) of West Nusa Tenggara (NTB) Province over the period 2004–2023. Existing empirical studies on regional economic growth in Indonesia yield inconsistent evidence regarding the contributions of labor quality, inflation dynamics, and human development, while long-term provincial-level analyses that simultaneously examine these variables remain scarce. To address this gap, this study applies multiple linear regression to secondary time-series data obtained from the Central Bureau of Statistics (BPS). The results indicate that the independent variables jointly exert a statistically significant influence on GRDP; however, only investment demonstrates a positive and significant individual effect, whereas labor, inflation, and HDI are statistically insignificant. These findings underscore the dominant role of investment in regional economic growth and suggest that improvements in labor and human